1969
DOI: 10.1901/jeab.1969.12-779
|View full text |Cite
|
Sign up to set email alerts
|

RUNNING‐WHEEL ACTIVITY AND AVOIDANCE IN THE MONGOLIAN GERBIL1

Abstract: In the first of two experiments, running-wheel activity and unsignaled (Sidman) avoidance were studied in gerbils and albino rats. All gerbils ran at higher rates than any of the four rats studied. Under the avoidance procedure, four rats developed effective responding; the other two performed much less successfully. While avoidance developed more slowly in the gerbils, all showed asymptotic performance as effective as the four superior rats. The rats showed a consistent warm-up effect, receiving 60% to 80% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

1970
1970
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 10 publications
(14 reference statements)
4
26
0
Order By: Relevance
“…The present findings apparently retlecl the fact that gerbils are more active (powell & Peck, 1969) and more exploratory (Glickman & Hartz, 1964) than rats. As GaIvarmi et al (1975) and Lippman et aI.…”
Section: Discussionsupporting
confidence: 71%
“…The present findings apparently retlecl the fact that gerbils are more active (powell & Peck, 1969) and more exploratory (Glickman & Hartz, 1964) than rats. As GaIvarmi et al (1975) and Lippman et aI.…”
Section: Discussionsupporting
confidence: 71%
“…Warm-up has been reported in both signalled avoidance (Hoffman, Fleshler, and Chorny, 1961) and unsignalled avoidance situations (Ulrich, Holz, and Azrin, 1964;Powell and Peck, 1969). Domesticated rats show this behavioral pattern indefinitely, regardless of their terminal performance during the preceding session.…”
Section: Methodsmentioning
confidence: 98%
“…Values of the intensity-duration product could be selected to produce just about any degree of warm-up, from none to a marked amount of shock disproportionality. Powell and his colleagues (Powell, 1971(Powell, , 1972Powell and Mantor, 1970;Powell and Peck, 1969) have suggested that the warm-up phenomenon is specific to domesticated laboratory rodents. The present data suggest that studies of avoidance behavior with wild and domesticated rodents slhould be conducted while varying the intensity-duration product.…”
Section: Apparatusmentioning
confidence: 99%
“…This phenomenon has been called warm-up (Hoffman, Fleshler, and Chorney, 1961;Powell, 1971;Powell and Peck, 1969). In a signalled avoidance experiment, increases in shock voltage produced no stable changes in the shock disproportionality exhibited (Hoffman, et al, 1961).…”
mentioning
confidence: 99%